2017
DOI: 10.1515/afe-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper on the Crystallization Process, Microstructure and Selected Properties of CGI

Abstract: The paper presents the results of the research on the effect of copper on the crystallization process, microstructure and selected properties of the compacted graphite iron. Compacted graphite in cast iron was obtained using Inmold process. The study involved the cast iron containing copper at a concentration up to approximately 4%. The effect of copper on the temperature of the eutectic crystallization as well as the temperature of start and finish of the austenite transformation was given. It has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Carbon from reducing agent can be formed to inform of iron carbide in the ferrous alloy during reduction smelting for the recovery of iron from copper slag. Copper is used as an additive element to improve mechanical properties such as hardness, abrasion resistance and corrosion resistance in cast iron products [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon from reducing agent can be formed to inform of iron carbide in the ferrous alloy during reduction smelting for the recovery of iron from copper slag. Copper is used as an additive element to improve mechanical properties such as hardness, abrasion resistance and corrosion resistance in cast iron products [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [19][20][21] thoroughly described the outstanding properties of the CGI iron while comparing it with the Ductile Iron (DI). The properties of the modern ADI grades and their capability to replace the steel castings in some applications have been presented in [22,23]. Yearly production of steel castings oscillates at ca.…”
Section: Introductionmentioning
confidence: 99%
“…Their low density causes them to flow to the surface layer of the casting, thus reducing its quality. It thus seems obvious that sulfur in cast iron should be eliminated or reduced to a minimum during the nodularization process in mold; however, authors [9][10][11][12][13][14] noted that there is a certain minimum amount of sulfur in cast iron that is required to produce cast iron of an adequate quality due to the correct morphology of graphite precipitates. The authors [1] showed the production process of cast iron castings with vermicular graphite precipitates, where sulfur compounds were deliberately added into the liquid alloy.…”
Section: Discussionmentioning
confidence: 99%